Case report: Mucous membrane pemphigoid with complicated autoantibody profile indicating the necessity of comprehensive diagnostic methods and the contribution of IgA autoantibodies - Liu, Weijun; Li, Huicheng; Jin, Yun; Cheng, Lifang; Shi, Luhuai; Gao, Yangmin; Zhou, Zhijun; Feng, Suying; Qian, Hua; Hashimoto, Takashi; Li, Xiaoguang (Frontiers in Immunology, 2023)
Mucous membrane pemphigoid (MMP) is a type of subepithelial autoimmune bullous disease, affecting various mucosae, occasionally with skin lesions. Both diagnosis and treatment of MMP are difficult. Although multiple autoantigens have been identified for MMP, the pathogenesis of MMP is still unclear. In this study, we presented a female MMP case with extensive oral mucosal lesions and skin lesions, particularly on the extremities. IgG and IgA autoantibodies against multiple autoantigens including BP180, laminin 332, integrinα6β4 and desmoglein 3, and IgM autoantibodies against BP180 were identified during the disease course. Compared with IgG autoantibodies, the levels of IgA autoantibodies against various autoantigens decreased more significantly with improvement of clinical features after the initiation of treatments. Our findings indicated the importance of comprehensive autoantibody screening for different immunoglobulin types and autoantigens at multiple time points for the precise diagnosis of various autoimmune bullous diseases, and the significant involvement of IgA autoantibodies into the pathogenesis of MMP.